ANALISIS KESALAHAN PENGGUNAAN TANDA BACA KARYA TULIS MAHASISWA MENGGUNAKAN BANTUAN KECERDASAN BUATAN CHATGPT - Shodiq, Jafar; Harsiati, Titik; Zahro, Azizatuz (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
This research aims to analyze punctuation errors in students' academic papers with the help of artificial intelligence, using ChatGPT as an evaluation tool. The scope of this research focuses on the identification and classification of punctuation errors, such as the use of commas, periods, and capital letters, which are often found in students' academic papers. The research method used is a qualitative approach with a content analysis method, in which data in the form of texts of student papers are analyzed using the automatic correction model of ChatGPT. The analysis is carried out by comparing the ChatGPT correction results with writing rules based on the General Guidelines for Indonesian Spelling (PUEBI). Translated with www.DeepL.com/Translator (free version) The research data model consists of samples of student papers covering various disciplines, with variations in sentence structure complexity to ensure diversity of findings. The results show that the most dominant punctuation errors are the improper use of commas in compound sentences and lists, as well as the improper use of capital letters in proper names and certain terms. An interesting fact found was that ChatGPT was able to provide fast and accurate corrections in most cases, but had limitations in understanding the context of ambiguous or creative sentences. This research confirms that artificial intelligence can be an effective tool in improving students' writing skills while supporting the writing process.